Experiences of Norwegian co-parents during COVID-19 pandemic restrictions: A qualitative study - Heidi Jerpseth; Anne Kaasen; Sara Rivenes Lafontan; Tine Schauer Eri (International Journal of Qualitative Studies on Health & Well-Being, 2023)
Purpose The COVID-19 pandemic restrictions have had a major impact on the organization of health services in Europe. Co-parents’ experiences of not being allowed to fully participate during pregnancy, childbirth, and the postpartum period is poorly understood. We investigated how the non-birthing partner experienced becoming a parent during the pandemic. Methods We applied a qualitative design. We recruited the participants from all part of the country by using snowball sampling. 18 individual interviews were conducted by using videotelephony software program/telephone. The transcripts were analysed using a six-step model for thematic analysis. Results The non-birthing participants were not considered by the healthcare system to be equal partners in terms of their involvement in the process of becoming parents. Three themes were constructed from the interview analysis- deprivation of the opportunity of “doing their part” of the job; participation by proxy to enhance togetherness; and choosing between obedience or opposition to the restrictions. Conclusion The non-birthing co-parents felt deprived of doing what they considered to be their most important job—namely, to support and comfort their partners during pregnancy and childbirth. The healthcare system’s decision to exclude co-parents from being physically present thus requires further reflection and discussion.